Meta-analysis of the response of broilers to the digestible lysine intake - Gobi, Jaqueline de Paula [UNESP] (2015)
Numerous publications are being published evaluating the effects of lysine intake on broiler performance, however, showing differing results mainly due to the variability in the experimental conditions. A meta-analysis was conducted to address the available information in this research field and study the response of lysine in diets for broilers. Data of 104 dose-response experiments testing different dietary lysine levels for 66.726 broilers were used in this database. Codifications were used with qualitative grouping criteria and as moderating variables in the analysis. The database was subdivided into four groups, which were: males in initial phase (from 1 to 21 days of old); males in growth phase (from 22 to 42 days of old); females in initial phase (from 1 to 21 days of old); and females in growth phase (from 22 to 42 days of old). Graphical analyses were used to explore the database, whereas equations were used to study study the response of dependent variables in each group previously described. These equations were generated through sequential analysis using fixed-effects and random-effects models. Lower variance responses were observed in models fitted using data of male broilers comparing to the female treatments. Using random components allowed the models to account for the variability in the database and to reduce the variance by 67% in average for males and females in initial and growing comparing to the fixed-effect model. Average Daily Gain was maximized at dietary digestible lysine intake of 0,526 and 1,364 grams day-1 for males in the initial and growth phases ...